PENGARUH MANAJEMEN SUMBER DAYA MANUSIA TERHADAP BUDAYA KERJA DI MIN 1 BOGOR - Wina Herdiana; Ahmad Idhofi; Agus Ali (Institut Ummul Quro Al-Islami Bogor, 2024)
Human resource management plays a central role in general education, being a key factor in achieving organizational goals. Success in the field of education largely depends on the effective management of human resources, which are considered a key component of the entire organization's resources. This study aims to explore five key indicators used to assess the effectiveness and efficiency of human resource management in general education: recruitment, leadership, human resource development, remuneration, and evaluation. The research method involves the analysis of key aspects of human resource management in general educational institutions, with data obtained through literature observation as well as possible interviews or questionnaires. The results showed that these five indicators had a significant effect, with leadership being a key factor in shaping work culture. The conclusion of the study is that human resource management in general education plays an important role in achieving organizational goals, and leadership has a major impact in creating a work culture that supports optimal human resource development. Therefore, the role of the principal is very important in shaping and maintaining a work culture that encourages employee performance and development